Emotions and the heart - G. V. Pogosova; I. E. Koltunov; Yu. S. Belova; N. V. Skazin (Кардиоваскулярная терапия и профилактика)
The article is devoted to most frequent psychopathological states in cardiac patients. Clinical, prognostic, and social role of these problems is considered in the cardiac continuum context. The forthcoming journal publication of the relevant clinical recommendations is announced.